The impact of alternative environmentally differentiated fairway dues systems in Sweden - Inge Vierth; Magnus Johansson (Journal of Shipping and Trade (JST), 2020)
The Swedish system for determining fairway dues at the national level is acknowledged as being unique in attempting to consider the environmental performance of vessels. Between 1998 and 2014, vessels could get a SOX discount and between 1998 and 2017 a NOx discount, both based on certificates. In 2018, the Swedish government initiated a new system comprising more environmental impacts requiring operators that want to benefit from it, to register their vessels for a score in the Clean Shipping Index (CSI). The CSI covers performance in five categories: NOX, CO2, SOX/PM, Chemicals and Waste. Based on received scores, vessels can get 10%, 30% or 90% discount. In this paper, the short-term outcome of the new system is analysed and compared to the old NOX-based system. The comparison is based on revealed preferences of the involved vessel operators. Vessel specific data about the discounts and scores are analysed as well as the regional distribution of discounts and impacts on different vessel types. The paper shows that the Swedish Maritime Administration has succeeded in creating a system that attracts more vessel types and encompasses more environmental categories, but that the incentives to reduce NOX emissions have been reduced. Ex-post cost-benefit analyses of the earlier certificate-based systems have proven them beneficial to society. However, it is unclear how the outcome of the new system will be. The paper suggests that there are efficiency gains in harmonising the system SMA has introduced with the different systems for environmentally differentiated port fees in Sweden.
Keywords: 650; Cost-benefit analysis; Environmental impact; NOx emissions; Shipping